The Trilogy of Islamic Epistemology: Integrating Bayani, 'Irfani, and Burhani in Modern Islamic Educational Research - Fikri Al Ghifar; Maspuroh; Natasya Ramadina Azura; Syifa Alawiyah; Hudallah (Penerbit Hellow Pustaka, 2025)
Epistemology within the Islamic educational tradition serves as a critical philosophical anchor for understanding the nature, acquisition, and sources of knowledge. This paper examines the